Penerapan Layanan Konseling Pribadi Bagi Remaja Putus Sekolah Di Lingkungan Masyarakat Desa Tuapakas Kecamatan Kualin Kabupaten Timor Tengah Selatan: Indonesia - Yando Abia Taneo; Ferdinan L. Lopo; Juniati A. Maak (Universitas Persatuan Guru 1945 NTT, 2026)
The purpose of this research is to explore the implementation of career counseling services for school dropout adolescents in the Tuapakas Village community, Kualin District, South Central Timor (TTS) Regency. This study uses a qualitative descriptive method with observation and interview techniques. The research was conducted in Tuapakas Village, involving 8 participants, consisting of 1 guidance and counseling teacher and 7 adolescents who have dropped out of school. The findings reveal that school dropout is caused by various factors, including economic conditions, household responsibilities, early marriage, and feelings of boredom or pressure at school. These results are in line with the Ecological Systems Theory by Bronfenbrenner, updated by Narayan (2016), which states that individual development is heavily influenced by surrounding systems such as family, local economy, community culture, and access to public services. For instance, one respondent dropped out of school due to economic hardship and chose to work on a farm, illustrating how the microsystem (family) and mesosystem (village environment) influence educational continuity.